Transient aerodynamic performance of high-speed trains when passing through an infrastructure consisting of tunnel–bridge–tunnel under crosswind. (August 2020) - Deng, E; Yang, Weichao; He, Xuhui; Ye, Yichao; Zhu, Zhihui; Wang, Ang
Highlights: The calculation scheme of aerodynamic load of HST is optimized. The aerodynamic difference mechanism between the 'OUT' and 'IN' processes is revealed. The interaction mechanism between resultant wind angle and jet flow is revealed. Abstract: The running safety risk of a high-speed train (HST) deteriorates remarkably under crosswind when the train drives into a bridge from a tunnel (OUT) or from a bridge into a tunnel (IN). This study aims to reveal the difference in the aerodynamic performance of HSTs in the two processes in terms of transient aerodynamic loads and flow field. A calculation approach for aerodynamic loads in which the carriage surface is divided into segments in longitudinal and circumferential directions is proposed to obtain the real-life time history of aerodynamic loads. The main results can provide a theoretical basis for traffic safety command when HSTs run in an infrastructure scenario consisting of tunnel–bridge–tunnel (ISTBT). In the presence of crosswinds, the maximum fluctuation amplitudes of five aerodynamic coefficients in the processes 'OUT' and 'IN' are increased by 2.1–83.8 and 4.0–84.3 times, respectively. The fluctuation amplitudes of five aerodynamic coefficients in the process 'IN' are generally 1.01–2.32 times larger than those in the process 'OUT' in a crosswind environment. A large resultant wind angle causes the fluctuation amplitudes in the five aerodynamic coefficients in the process 'IN' to be larger than those in the process 'OUT'. The maximum fluctuation amplitude of aerodynamic coefficients in leading and tail carriages is the key to controlling traffic safety when HSTs run in ISTBT in a crosswind environment.